Andryoides gen. n. and morphological key features in cestodes of the family Anoplocephalidae sensu stricto (Cyclophyllidea) in mammals - Haukisalmi, Voitto (Folia parasitologica, 2023)
As presently defined, the tapeworm genus Andrya Railliet, 1895 (Cyclophyllidea: Anoplocephalidae sensu stricto) includes the type species A. rhopalocephala (Riehm, 1881) in hares of the genus Lepus Linnaeus (Leporidae) in western Eurasia and four species in cricetid (Neotominae, Sigmodontinae) and octodontid rodents in North and South America. The host range of Andrya is puzzling, because it is the only genus of anoplocephalid (s. s.) cestodes parasitising both rodents and lagomorphs. The present morphological analysis shows that the American species of Andrya share multiple consistent features, in which they differ from those of A. rhopalocephala and the morphologically related Neandrya cuniculi (Blanchard, 1891). The main differences concern the position of the uterus with respect to the longitudinal osmoregulatory canals and testes. Consequently, a new genus Andryoides gen. n. is proposed for the American species, resulting in the following combinations: Andryoides neotomae (Voge, 1946) comb. n. (type species), Andryoides octodonensis (Babero et Cattan, 1975) comb. n., Andryoides vesicula (Haverkost et Gardner, 2010) comb. n. and Andryoides boliviensis (Haverkost et Gardner, 2010) comb. n. However, A. boliviensis is regarded here as a junior synonym of A. vesicula (new synonymy). The present study also defines the morphological key features for all the valid genera of cestodes of the family Anoplocephalidae (s. s.), and discusses the phylogenetic affinities and historical biogeography of Andryoides and other endemic American anoplocephalid cestodes.
Keywords: Animals; Mammals; Female; Cestoda; Rodentia; ženské pohlaví; cestodózy; Arvicolinae; Andrya; Phylogeny; savci; Cricetidae; Octodontidae; new genus; hlodavci; Cestode Infections; zvířata; fylogeneze; Sigmodontinae; Neandrya